Semifluorinated alkanes as new drug carriers - an overview of potential medical and clinical applications - Tsagogiorgas, Charalambos; Otto, Matthias (Pharmaceutics, 2023)
Fluorinated compounds have been used in clinical and biomedical applications for years. The newer class of semifluorinated alkanes (SFAs) has very interesting physicochemical properties including high gas solubility (e.g., for oxygen) and low surface tensions, such as the well-known perfluorocarbons (PFC). Due to their high propensity to assemble to interfaces, they can be used to formulate a variety of multiphase colloidal systems, including direct and reverse fluorocarbon emulsions, microbubbles and nanoemulsions, gels, dispersions, suspensions and aerosols. In addition, SFAs can dissolve lipophilic drugs and thus be used as new drug carriers or in new formulations. In vitreoretinal surgery and as eye drops, SFAs have become part of daily clinical practice. This review provides brief background information on the fluorinated compounds used in medicine and discusses the physicochemical properties and biocompatibility of SFAs. The clinically established use in vitreoretinal surgery and new developments in drug delivery as eye drops are described. The potential clinical applications for oxygen transport by SFAs as pure fluids into the lungs or as intravenous applications of SFA emulsions are presented. Finally, aspects of drug delivery with SFAs as topical, oral, intravenous (systemic) and pulmonary applications as well as protein delivery are covered. This manuscript provides an overview of the (potential) medical applications of semifluorinated alkanes. The databases of PubMed and Medline were searched until January 2023.